2011
DOI: 10.2478/s11534-011-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the amorphous carbon films by the ns-laser irradiation

Abstract: Abstract:The effect of a nanosecond laser irradiation of thin (60 and 145 nm) amorphous, diamond-like carbon films deposited on Si substrate by an ion beam deposition (IBD) from pure acetylene and acetylene/hydrogen (1:2) gas mixture was analyzed in this work. The films were irradiated with the infrared (IR) and ultraviolet (UV) radiation of the nanosecond Nd:YAG lasers working at the first (1.16 eV) and the third (3.48 eV) harmonics, using a multi-shot regime. The IR laser irradiation stimulated a minor incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thin DLC films being transparent in the infrared region are resistant to IR-laser irradiation. This fact could be used to modify the film-substrate interface as it was shown in [187,188]. Irradiation by the first harmonics of a Nd:YAG laser (1.16 eV) stimulated formation of SiC and a slight hydrogenization of Si at the DLC-Si interface region.…”
Section: Ultrafast Lasers For Micromachining Of Composite Matmentioning
confidence: 89%
“…Thin DLC films being transparent in the infrared region are resistant to IR-laser irradiation. This fact could be used to modify the film-substrate interface as it was shown in [187,188]. Irradiation by the first harmonics of a Nd:YAG laser (1.16 eV) stimulated formation of SiC and a slight hydrogenization of Si at the DLC-Si interface region.…”
Section: Ultrafast Lasers For Micromachining Of Composite Matmentioning
confidence: 89%
“…These results are in agreement with the works of Kononenko et al [47] on laser-induced mechanisms in DLC films showing that the absorbed laser pulse produces an expansion of surface layer and reduces its mass density. Furthermore, Grigonis et al [5] demonstrated that the conversion of the sp 3 to sp 2 sites caused the swelling.…”
Section: Irradiation Of Thin Film By Uv Nanosecond Pulsed Lasermentioning
confidence: 99%
“…Amorphous carbon (a-C) is widely reported in the literature and used in many applications due to the large adaptability of its properties [1][2][3][4][5][6][7][8][9][10]. Its structure contains short range ordered domains mixing three hybridizations sp, sp 2 and sp 3 with different proportions of each them depending on deposition experimental parameters which in turn determines their properties.…”
Section: Introductionmentioning
confidence: 99%
“…The doped DLC fi lms are deposited by the same techniques as carbon fi lms (see Section 4.3), adding the doping-carrier species to the deposition environment (Grill, 1999). Other types of surface modifi cation, such as gas plasma treatments, infrared or ultraviolet irradiation by nanosecond laser, have also been used to change the surface properties of DLC fi lms (Mochizuki et al , 2011;Grigonis et al , 2011).…”
Section: Modifi Ed Dlc Fi Lmsmentioning
confidence: 99%